2023
DOI: 10.1186/s12915-023-01538-w
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenomics revealed migration routes and adaptive radiation timing of Holarctic malaria mosquito species of the Maculipennis Group

Abstract: Background Phylogenetic analyses of closely related species of mosquitoes are important for better understanding the evolution of traits contributing to transmission of vector-borne diseases. Six out of 41 dominant malaria vectors of the genus Anopheles in the world belong to the Maculipennis Group, which is subdivided into two Nearctic subgroups (Freeborni and Quadrimaculatus) and one Palearctic (Maculipennis) subgroup. Although previous studies considered the Nearctic subgroups as ancestral, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 84 publications
(114 reference statements)
0
5
0
Order By: Relevance
“…melanoon. Only one autosomal inversion became fixed after the split between the European clade and the Northern Eurasian clade about 10.5 million years ago [8]. According to our reconstruction, the X chromosome of An.…”
Section: Discussionmentioning
confidence: 73%
See 4 more Smart Citations
“…melanoon. Only one autosomal inversion became fixed after the split between the European clade and the Northern Eurasian clade about 10.5 million years ago [8]. According to our reconstruction, the X chromosome of An.…”
Section: Discussionmentioning
confidence: 73%
“…Two nested inversions were identified in the X chromosome, which were fixed in the An. messeae lineage after its separation from other species of the Maculipennis subgroup about 7.9 million years ago [8]. The comparison of gene orders in the BRs with those in outgroup species has shown that An.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations